PECULIARITIES OF MOTHER'S PARENTAL BURNOUT IN WAR TIMES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2024)
Background. In the process of interaction with children, parents face various difficulties that affect their psycho-emotional state. In the conditions of the long war with Russia, in addition to daily routine difficulties, Ukrainian mothers faced the need to protect the life and health of their child in conditions of constant shelling and a real threat to life. Added to this are a number of stressors associated with serious losses: work, health, loved ones, moving to another city or to another country. Prolonged emotional stress associated with existential threat leads to exhaustion, which can lead to increased levels of parental burnout, affect family interpersonal relationships, and increase levels of child neglect and family violence. The aim of our study was to find correlates of parental burnout in women during the war, which are related to the peculiarities of the functioning of the family system and ways of coping with stress (coping strategies) of women.Methods. To achieve the goal of the study, a questionnaire was used, which included the collection of information on the socio-demographic characteristics of the subjects, the "Parental Burnout Questionnaire" by M. Mikolajczak and I. Roskam, the codependency questionnaire by J. Weinhold, the FACES family adaptation and cohesion scale by D. Olson, the coping assessment questionnaire – COPE strategies by K. Carver.Results. The conducted research made it possible to assess the level and characteristics of the manifestation of parental burnout among Ukrainian women during the war. Among the four parameters of burnout, exhaustion from motherhood has the highest level of expression, a quarter of the respondents demonstrate high and very high levels of parental burnout in general. A significant relationship between the characteristics of coping behavior, codependence of a woman, the age of the youngest child and cohesion as a characteristic of the family system was revealed. The most significant predictors of a woman's parental burnout were the level of codependence of a woman, the age of her youngest (or only) child, and the strategy of active coping in difficult life situations.Сonclusions. The obtained results can serve as a basis for further studies of parental burnout of women in Ukraine, as well as for the development of tools for providing psychological assistance to women who have its signs, for the search for resource strategies for coping behavior and the factors underlying it.
Keywords: burnout; codependency; coping strategy; family cohesion; family system; women's parental burnout; parenting; stress